No double standards: Quantifying the impact of standard harmonization on trade - Julia Schmidt; Walter Steingress (Bank of Canada, 2019)
Product standards are omnipresent in industrialized societies. Though standardization can be beneficial for domestic producers, divergent product standards have been categorized as a major obstacle to international trade. This paper quantifies the effect of standard harmonization on trade flows and characterizes the extent to which it changes the cost and demand structure of exporting. Creating a novel and comprehensive database on crosscountry standard equivalences, we identify standard harmonization events at the document level. Our results show that the introduction of harmonized standards increases trade through a larger sales volume of existing exporters (intensive margin) and more entry (extensive margin). These findings are consistent with a multi-country heterogeneous firm model featuring endogenous standard adoption. Because of additional demand, standard harmonization raises firms' incentives to produce varieties in accordance with the standard despite high sunk investment costs. Firms' export sales expand and entry into foreign markets is encouraged.
Keywords: F13; F14; F15; L15; 330; Econometric and statistical methods; International topics